Modelling Mediterranean pasture dynamies (Plant Ecology, 1989)
Pasture vegetation in an open woodland of Quercus rotundifolia subjected to periodic ploughing was sampled in spring during 8 consecutive years. The frequency of herbaceous species was recorded in a total of 69 permanent plots located on 5 adjacent sites with similar lithology, slope and orientation but differing in age since previous ploughing. Vegetation dynamics expressed as trajectories of permanent plots in a non-metric multidimensional scaling space has been modelled in terms of evironmental variables. By fitting a generalized linear model, the dynamics are shown to be related to years since last ploughing, geographical location of plots, total annual rainfall and November rainfall. Meteorological patterns of the sampling period are also described